Altruism, favoritism, and guilt in the allocation of family resources: Sophie's choice in Mao's mass send down movement - Hongbin Li; Mark Richard Rosenzweig; Junsen Zhang (Yale University, Economic Growth Center, 2008)
In this paper, we use new survey data on twins born in urban China, among whom many experienced the consequences of the forced mass rustication movement of the Chinesecultural revolution, to identify the distinct roles of altruism and guilt in affecting behavior within families. Based on a model depicting the choices of the allocation of parental time and transfers to multiple children incorporating favoritism, altruism and guilt, we show the conditions under which guilt and altruism can be separately identified by experimental variation in parental time with children. Based on within-twins estimates of affected cohorts, we find that parents selected children with lower endowments to be sent down; that parents behaved altruistically, providing more gifts to the sibling with lower earnings and schooling; but also exhibited guilt given the current state variables of the two children, the child experiencing more years of rustication received significantly higher transfers.
Keywords: J12; J13; O12; 330; Guilt; altruism; China